ACTING SCHOOL AT THE NAMANGAN REGIONAL MUSICAL DRAMA THEATER: (IN THE CASE OF ONAKHON TOJIBOYEVA) (International journal of artificial intelligence, 2026)
This article examines the creative work of the Honored Artist of Uzbekistan, Onakhon Tojiboeva, who is an integral part of the history of the Namangan Regional Musical Drama Theater. From an art historical perspective, the article analyzes the creative processes in the theater during the 1940s-1970s, the actress's mastery in musical and dramatic performances, and her unique style in creating lyrical and strong-willed female characters.